ETR 300 D'Bes Arena / Mohamad Azahan Mohd Othman… [et.al] - Mohd Othman, Mohamad Azahan; Abdullah, Mohammad Ekhsan; Kamis, Sudiman; Gala, Joseph Kimmy; Sonti, Adderly (2012)
There are many factors that encourage us to open up a sport facility in Mukah. First, there’s only one indoor stadium in Mukah. Therefore, there is not many competitors that will compete.Second is to provide facility to local people in Mukah area. By doing so, they can spend their time on useful activity, especially for teenagers. We also want them to practice healthy lifestyle.Rather than wasting their time, they can enjoy sport. Last is to gain profit. We need to make money so that we can provide a good facility and can maintain our business.